Understanding the successful improvement of co-development - Jukes, Sarah (Cranfield University, 2000)
Through increasingly efficient mass-production techniques, car-ownership has been made affordable to a large segment of the world's population, beginning in Europe and North America in the first decades of this century and recently extending rapidly throughout all other continents. The industry, however, is running out of major new opportunities for growth, and automotive markets in the Western World have entered the phase of maturity; this is typified by slowing growth and intensifying competition. These factors are driving fundamental change in the economics of the industry, and are forcing rationalisation and consolidation across the world. In a drive to remain competitive, the major Vehicle Manufacturers are relying more and more on the capabilities of their first-tier suppliers, and are pushing design and development responsibility further down the supply chain; suppliers are taking on a new role within the automotive industry and are increasingly becoming involved in the design and development of new products in collaboration with their major customers. The core theme throughout this research enquiry has been to investigate such practices (which have been termed co development), with particular emphasis placed on the European automotive industry. The literature within the areas of customer-supplier relationships and product development is wide and varying, and both bodies of knowledge are beginning to stress the importance of co-development in a number of industries. However, even though academics and industrialists are suggesting co development is necessary in today's marketplace, research into this area remains scarce and few insights into the improvement of such relationships can be found. This research has begun to close this gap by identifying those factors that can influence the successful transformation of co development. Through a series of focus groups, fifty-two concepts were identified that were seen to influence the success of co-development improvement activity - due to the nature of the focus group methodology, these concepts were wide-ranging and covered all aspects of the cross-company relationship, highlighting many -areas for further investigation. These concepts were reviewed and grouped, and four concepts plus sixteen sub-concepts chosen for additional analysis - these include a preparation phase, in which both organisations recognise the need for improvement and commit to enhance their existing relationship, the nature of communication across organisational boundaries, the alignment of working practices at all levels of the business, and an implementation phase in which actual improvements are realised and further sustained. These have been represented in an initial conceptual model that simply depicts the interdependencies that exist between the four high-level concepts. This conceptual model has been further tested and expanded through seven case studies; six cases were conducted at first-tier suppliers, whilst one was completed within a European-based VM. The major data collection tool used during these studies was the semi-structured interview, providing deep insights into co-development improvement from both sides of the relationship. The case studies only reiterated the importance of the concepts and sub-concepts within a co-development environment, and provided insights into the 'who, what, where, when, and how' of the topics under consideration. Finally. the concepts have been validated through a twelve-month action-research study, involving the actual implementation of the conceptual model in an industrial setting. The researcher gained first hand experience of co-development improvement, and observed an organisation struggling with the complexities of the cross-company environment. The knowledge gained throughout this period has not only emphasised the importance of the concepts and sub-concepts to co-development improvement, but has provided future implementers with insights into how one organisation has successfully transformed forty of their co-development relationships.